KONTRIBUSI USAHATANI TANAMAN JAGUNG PROGRAM PHBM TERHADAP PENDAPATAN PENDUDUK DESA KALIGAYAM KECAMATAN MARGASARI KABUPATEN TEGAL - Afiati, Ratih; Eva, Banowati; Ananto, Aji (Geo-Image, 2018)
The Community-based Forest Management (in Indonesian called Pengelolaan Hutan Bersama Masyarakat ? PHBM) program initiated to give opportunities for the villager of forest to earn an income that can be used to meet of the living cost participants of the program. In the Kaligayam Village the PHBM program utilized pesanggem for the corn farming. With that case this study aims 1) to know factors that affect corn crop production. 2) to know the corn cultivation techniques which is done by the farmers. 3) to analyze how big contribution of the corn crop production in favoring Kaligayam villagers' revenue. The research used quantitative research metod, with the population consisted of the board of Forrest Village ( in Indonesian called Lembaga Masyarakat Desa Hutan ? LMDH). The analysis technique which was used was the analysis of the household income of Pesanggem and analysis of the farming contributions. In this study, there is dominant factor which affect the corn production was the land area. The corn farming gave average contribution about Rp. 1.338.005 per month, while total villagers? income was about Rp. 4.785.277 per month. than the corn farming in the Kaligayam Village of Margasari District Tegal Regency gave low contribution that was 27.96% of the total income received by the households of Pesanggem.